SPE Annual Technical Conference and Exhibition 1994
DOI: 10.2118/28627-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Validation of Phase Behaviour Models for Reservoir Studies of Gas Injection Schemes

Abstract: Compositional models based on cubic equations of state (EOS) are generally employed for simulation of the reservoir performance in gas injection processes. Tuning of the EOS to experimental equilibrium data generated at static conditions, PVT data, prior to its use for compositional studies is the current practice in the oil industry. The displacement of oil in a slim tube by the injection gas simulates the phase behaviour resulting from the continuous contact between the two phases in the reservoir more reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Khazam et al (4) conducted a set of slim tube experiments to investigate the effect of IFT on relative permeability curves. They showed that as IFT approaches zero, that is approaching miscibility, the residual oil saturation, the immobile oil left behind, decreases toward zero and the relative permeabilities increase.…”
Section: Ift Reduction and Relative Permeability Curvesmentioning
confidence: 99%
“…Khazam et al (4) conducted a set of slim tube experiments to investigate the effect of IFT on relative permeability curves. They showed that as IFT approaches zero, that is approaching miscibility, the residual oil saturation, the immobile oil left behind, decreases toward zero and the relative permeabilities increase.…”
Section: Ift Reduction and Relative Permeability Curvesmentioning
confidence: 99%